Upaya Penurunan Kejadian Kehilangan Gelas Berukuran Sedang Melalui Penerapan Metode Quality Control Circle (QCC) di Unit Gizi, RS ABC, Jakarta - Jonny, Jonny (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Nutrition Department of ABC Hospital provides food and beverage for all inpatients based on nutrition standard from their practioners. Therefore, Nutrition Department needs several types of cutlery for serving them food and beverage as needed. The stock of these types of cutlery should be maintained by nutrionists. During August and September 2011, the stock of middle-sized glasses had been deficit. This condition made the Nutrition Department initiate a QCC group named Sushi to prevent the deficit by strengthening the control over the stock. After this improvement, they had successfully suppressed the deficit from 193 to 77 units or 60.10%. Due to hospital regulation that every lost should be redeemed by nutritionist, this improvement had also enable the department to suppreesed the cost of lost units (quality cost).